Analisis Permintaan Karet Alam Indonesia di Pasar Internasional - Purnomowati, Happy Dewi; Darwanto, Dwidjono Hadi; Widodo, Sri; Hartono, Slamet (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2015)
The development of the natural rubber market in three years was relatively favorable for producers, which was indicated by the relatively high price level. This was due to increasing demand. Of course this will be a good opportunity for Indonesia to export processed rubber and rubber industry in Indonesia to other countries. The purpose of this study was to determine the factors that can affect demand for Indonesias natural rubber exports in each countrys export destinations. The data used was secondary data years 1980-2013 time series derived from IRSG, BPS, FAO, Gapkindo, UN Comtrade, BI, and the World Bank. Methods of analysis using dynamic demand model